2017
DOI: 10.2196/mhealth.8349
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Intervention to Increase Oral Cancer Therapy Adherence in Patients With Chronic Myeloid Leukemia (The REMIND System): Clinical Feasibility and Acceptability Assessment

Abstract: BackgroundOptimal dosing of oral tyrosine kinase inhibitor therapy is critical to treatment success and survival of patients with chronic myeloid leukemia (CML). Drug intolerance secondary to toxicities and nonadherence are significant factors in treatment failure.ObjectiveThe objective of this study was to develop and pilot-test the clinical feasibility and acceptability of a mobile health system (REMIND) to increase oral drug adherence and patient symptom self-management among people with CML (chronic phase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 61 publications
1
47
0
1
Order By: Relevance
“…The body of current literature suggests that this area of research and practice is still under development. While several studies assessing the feasibility of digital PPC interventions have shown good acceptance among the users, empirical research needs to move beyond feasibility studies and include efficacy trial with large samples in order to provide critically needed evidence to inform development and dissemination of digital PPC interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The body of current literature suggests that this area of research and practice is still under development. While several studies assessing the feasibility of digital PPC interventions have shown good acceptance among the users, empirical research needs to move beyond feasibility studies and include efficacy trial with large samples in order to provide critically needed evidence to inform development and dissemination of digital PPC interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 5 studies, 3 included participants with diverse types of cancer [17-19], 1 focused on patients with chronic myeloid leukemia [20], and 1 focused on breast cancer patients [21]. All the studies focused on adult participants (aged >18 years).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 2 distinct methods were used to deliver the interventions: SMS text messages and mobile apps. The SMSs were sent as medication intake reminders and frequency was daily or twice daily according to individual medication intake schedules [17,20]. The SMS reminders were bidirectional (participants’ response “Y” or “N” was expected) to collect data on the frequency of taking medication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations